Assessment of Cost of Illness and Satisfaction with Life in Hypothyroidism Patients at Tertiary Care Centre, Erode- A Prospective Observational Study - S, Srinivasan; Nandhini, Hema; Prakasam, Arul; Kumar, Senthil (Indian Journal of Pharmacy Practice)
Background: Recent research has highlighted the significant economic burden associated with hypothyroidism, showing that individuals affected by this condition experience increased healthcare costs due to both acute and chronic complications. This study aims to analyze the financial impact of treating hypothyroidism and to gauge the life satisfaction levels of patients undergoing treatment at a specialized hospital. Materials and Methods: This prospective observational study was conducted at a tertiary care hospital in Erode, Tamil Nadu, spanning 9 months from August 2023 to April 2024. The study enrolled 175 adult patients diagnosed with hypothyroidism who visited the outpatient department, excluding pregnant and lactating women, pediatric patients and those with irregular treatment adherence. Statistical analysis was performed using SPSS software with Student’s t-test and Paired t-test methods. Results: Females showed a higher prevalence of hypothyroidism than males, particularly among housewives. Around 42.86% of participants had a family income ranging from 20,000 to 30,000 rupees. The primary medication prescribed to most participants was Thyroxine 100 mcg. Initial visits incurred higher costs compared to subsequent ones, with direct costs comprising over 50% of the total expenditure. Before intervention, most participants were somewhat dissatisfied with treatment, but after intervention, they were generally more satisfied. Conclusion: The study found that participants initially expressed moderate dissatisfaction with their treatment. However, following the intervention, there was a notable increase in satisfaction, evident from significant improvements in their Satisfaction with Life Scale (SWLS) scores, highlighting an overall enhancement in their quality of life.
Keywords: Direct cost and Indirect cost; Hypothyroidism; Intervention